PENGARUH BULLYING,GOSIP DAN KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN PT SANGWOO INDONESIA - Karyono Karyono; Tesalonika Br Perangin Angin (GEMILANG: Jurnal Manajemen dan Akuntansi, 2022)
Bullying, gossip and organizational communication are very important in the world of work. Supported by a work environment that can provide a sense of security and comfort in working can create optimal performance. This study aims to describe and analyze the effect of bullying, gossip, and organizational communication and the work environment partially and simultaneously on employee performance and examine which variables have a dominant effect on employee performance at PT Sangwoo Indonesia. This study uses a qualitative approach. The data obtained from the results of interviews, observations, documentation, and focused discussions (Focus Group Discussion). The sampling method is Simple Random Sampling. The sample in this study was 168, the majority aged 22-27 years. This study was based on a confirmatory model study. Structural Equation Modeling with the help of SPSS statistics to test the validity and reliability of the instrument.